Diferenciación de leche y productos lácteos enriquecidos naturalmente en compuestos antioxidantes - Rossetti, Luciana (2015)
In order to add value to milk, assays were performed to improve antioxidant capacity through the diet of animals.\nFor basal data, milk from dairy farms and the diets used were assayed giving a correlation between them as well as a seasonal correlation. Incorporation kinetics of fresh pasture antioxidants into milk, showed that in 20 days the composition of milk was modified yielding a product with higher antioxidant capacity. Since production conditions do not always allow high pasture levels in the diet of dairy cows, two alfalfa concentrations during two different seasons were assayed. To determine the transfer of incorporated compounds into milk products, powdered milk and mature cheese were studied. It was estimated that pastures with aproximately 50% alfalfa would be able to modify the quality of milk and that the season influences the incorporation of these compounds. The characteristics of raw milk were transfered to milk products. The study of the shelf life of powdered milk showed that increased concentrations of liposoluble antioxidants were able to preserve it from oxidation effects.